(untitled) (Al-Qamar, 2023)
Linguistics is an ever growing subject. As much attention is required on linguistics in Urdu, the same amount of shortage is being faced. As many experts have written in Urdu linguistics till today, the feeling of thirst remains constant even after reading their books. The main reason for this is that the subject of linguistics is also borrowed from English like other subjects. Due to which the Urdu speaking class has to face difficulties. Ghazal has definitely come to this region through Arabic and Persian. But today in Ghazal, the kind of topics that have been described, huge heaps of manuscripts will not be enough to give the details. Just as Ghazal has been written with full devotion, we cannot be master in linguistics until we make sincere effort. A linguist has to consider the themes of formation, destiny, origin and evolution of language. As many theories of linguists have come to forefront about the structure and origin of language, each presents a new angle on the origin of language. After reading these different views, where the level of knowledge is expanding, the common readers also seem astonished as well. The need is that one center should be considered as the original and the future journey should be planned so that it may be easy and convenient for the beginners. In this article, a small attempt has been made to provide the reader with an introduction to the origin and evolution of linguistics and various branches of linguistics.